Sosialisasi Pemberdayaan Manajemen UMKM dan Strategi Pemasaran Produk dalam Meningkatkan Penjualan Usaha - Dian Rachmawati Afandi; Indra Permana; Muhamad Syahwildan; Arif Widodo Nugroho; Daspar Daspar (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Indonesian people are increasingly creative and innovative in making new recipes to add to their daily food needs, besides that they are also creative in making snacks typical of their region. Currently, according to young people and parents, snacks are much loved, besides that with a distinctive taste from the West Java region in the city of Bandung which is familiar to be heard or felt by people who mostly like snacks with a spicy taste, namely "Seblak". The business being run certainly requires a way to attract customers to come and try it, therefore it is necessary to hold consistent marketing, marketing is carried out by promotional activities which is one of the important ways to compete not based on price but taste quality. The results of observations that I have made meeting directly with seblak owners mention the problems faced by the lack of understanding of the management and business planning needed, especially in terms of marketing, which currently requires the use of technology in its implementation. MSME empowerment requires more comprehensive and systematic planning that is able to facilitate MSMEs in solving the problems they face. As well as readiness in the use of technology such as promotional activities that are not only carried out through automatic whatsapp with a limited range of buyers, followed by promotions carried out through social media such as Instagram and Facebook because they are social media that are used more frequently so that the sales market is also wider, and currently in the age of all technology we can also take advantage of technology to do business by selling products in marketplaces such as gofood, gojek, grab etc.. That way, increasing the empowerment of MSMEs is increasingly developing from various sides.